2019
DOI: 10.1111/gbb.12616
|View full text |Cite
|
Sign up to set email alerts
|

Maternal caregiving and DNA methylation in human infants and children: Systematic review

Abstract: The integration of behavioral epigenetics' principles (eg, DNA methylation) into the study of human infants' development has mainly focused on the effects of early adverse exposures, paying less attention to protective caregiving experiences. The present review focused on DNA methylation linked to variations in maternal behavior in human infants and children. Literature search occurred on three databases (PubMed, Scopus and Web of Science) and 11 records were selected. Key variables were abstracted from each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 88 publications
(294 reference statements)
0
40
0
Order By: Relevance
“…Although promising, the available body of evidence should be treated with caution as most studies until now have relied on relatively small sample sizes, often used a single candidate gene approach, and have been cross‐sectional—often retrospective—in research design. A recent review by Provenzi, Brambilla, di Minico, Montirosso, and Borgatti (2019) is illustrative of this trend, showing that out of 11 studies of methylation and maternal behavior only 4 ( n ≤ 128) had a prospective design. Moreover, although childhood adversity has been linked to differential DNA methylation, previous research has not established whether DNA methylation mediates a link between dysfunctional parenting and subsequent stress reactivity and disruptive behavior.…”
Section: (Epi)genetics In Parenting Effects On Disruptive Behaviormentioning
confidence: 99%
“…Although promising, the available body of evidence should be treated with caution as most studies until now have relied on relatively small sample sizes, often used a single candidate gene approach, and have been cross‐sectional—often retrospective—in research design. A recent review by Provenzi, Brambilla, di Minico, Montirosso, and Borgatti (2019) is illustrative of this trend, showing that out of 11 studies of methylation and maternal behavior only 4 ( n ≤ 128) had a prospective design. Moreover, although childhood adversity has been linked to differential DNA methylation, previous research has not established whether DNA methylation mediates a link between dysfunctional parenting and subsequent stress reactivity and disruptive behavior.…”
Section: (Epi)genetics In Parenting Effects On Disruptive Behaviormentioning
confidence: 99%
“…Increased prevalence of post-traumatic stress symptoms was reported in survivals of the SARS epidemic (10) and preliminary evidence of similar psychological effects are also emerging for the Covid-19 emergency (11). Notably, the stress perceived by parents may widely affect parenting behaviors (12) and the quality of parent-child interaction (13,14). Neuroscientific (15) and epigenetic (16) evidence suggests that these stress-related parenting effects may have profound intergenerational consequences for children's emotional and cognitive development (17)(18)(19).…”
mentioning
confidence: 92%
“…For example, research in animals, living humans, and postmortem human brains has shown associations between early environment (e.g. trauma) and DNA methylation [ 18 ▪ , 19 24 ]. Likewise, exposure to gestational distress (e.g.…”
Section: What Is Dna Methylation?mentioning
confidence: 99%